Aplikasi Ujian Tryout Berbasis Client Server Menggunakan Linier Congruent Method (LCM) Pada Sekolah Menengah Kejuruan - Haida Dafitri; Rachmat Aulia; Ari Usman; Jihan Nabila Fathia (Forum Kerjasama Pendidikan Tinggi, 2023)
Tryout in the scope of education in Indonesia is a trial that is usually carried out before facing the actual exam, or among students refers to a trial before facing a computer-based national exam (UNBK). The problem that has been identified is the implementation of the exam is still applying a traditional system that uses exam paper and fills in the answers themselves using pencils and pens. Therefore, this research focuses on designing a tryout exam application applying the linear congruent method held in schools, especially vocational high schools (SMK). This method is an algorithm used to generate random numbers. The function is to randomize questions, which can be defined as a mechanism for randomizing questions to create new questions that are different from the last. Hopefully, this application can help schools in terms of making, multiplying and distributing questions being tested. In addition, the results can be printed directly using a computer